Moral Decadence Among Students in the Digital Age: Challenges and Solutions in Learning Islamic Religious Education - Nafsia Marasabessy; Ruslan Dahinang; Wisriani; Muminaya; Amaluddin (Universitas Muhammadiyah Palu, 2026)
Moral decadence among students in the digital era has become an alarming phenomenon along with the massive penetration of technology in the lives of the younger generation. This research aims to analyze the characteristics and factors causing student moral degradation in the digital era, identify challenges faced in Islamic Religious Education learning, and formulate effective strategies and solutions in shaping students' noble character. The research method uses a qualitative approach with library research that relies on secondary data from various scientific literature. The research results show that student moral decadence is characterized by increasing deviant behaviors such as online game addiction, cyberbullying, and consumption of negative content triggered by internal factors in the form of weak understanding of religious values and external factors in the form of easy access to technology without adequate supervision. The challenges of Islamic Religious Education learning include curricula that are not yet adaptive, low digital competence of educators, and minimal synergy between schools, families, and communities. The recommended solutions include digital transformation of learning based on tafsir tarbawi, strengthening critical digital literacy, and building a collaborative and holistic moral education ecosystem to form a generation that has moral resilience in the digital era.